2001
DOI: 10.1054/bjoc.2001.1815
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of differentiation- and proliferation-inducers on Lewis antigens, α-fucosyltransferase and metastatic potential in hepatocarcinoma cells

Abstract: SummaryThe expressions of Lewis (Le) antigens, α-1,3/1,4 fucosyltransferases (α-1,3/1,4 FuTs), and metastatic potential after the treatment of 2 differentiation inducers, all-trans retinoic acid (ATRA), 8-bromo-cyclic 3′,5′adenosine monophosphate (8-Br-cAMP); and 2 proliferation inducers, epidermal growth factor (EGF) and phobol-12-myristate-13-acetate (PMA), on 7721 human hepatocarcinoma cell line were studied. Cell adhesion to human umbilical vein endothelial cells (HUVEC), cell migration through transwell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
(9 reference statements)
1
41
0
Order By: Relevance
“…We have found with Northern blot that the expression of a1,3 FucT-III and VI was very low in 7721 cells (Liu et al 2001a;2001b); the gene of a1,3 FucT-was reported to be silent in many tissues (Narimatsu 1998). We also found that the expression of a1,3 FucT-VII, but not a1,3/1,4 FucT-III and a1,3 FucT-VI, was increased after the transfection of the oncogene, c-erbB2/neu (Liu et al 2001a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found with Northern blot that the expression of a1,3 FucT-III and VI was very low in 7721 cells (Liu et al 2001a;2001b); the gene of a1,3 FucT-was reported to be silent in many tissues (Narimatsu 1998). We also found that the expression of a1,3 FucT-VII, but not a1,3/1,4 FucT-III and a1,3 FucT-VI, was increased after the transfection of the oncogene, c-erbB2/neu (Liu et al 2001a).…”
Section: Resultsmentioning
confidence: 99%
“…(3) cell adhesion to HUVEC, as well as cell migration and invasion were significantly abolished only by the specific monoclonal antibody of SLe x , KM93, suggesting that SLe x is the most important Lewis antigen responsible for the above metastasis-related phenotypes in FucT-VI, and their corresponding products, SLe a and SDLe x , were rather low in 7721 cells (Liu et al 2001a(Liu et al , 2001b, but that of a1,3 FucT-VII and its product, SLe x , were more expressed, indicating that a1,3 FucT-VII is the most likely enzyme in the synthesis of SLe x in 7721 cells. The expression of a1,3 FucT-VII was down-regulated after transfection of nm23-H1 and was not very obvious (maybe due to the sufficient expression of nm23-H1 in the parental 7721 cells), but this result was repeatable and statistically significant in clones 3 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has demonstrated that surface SLe x is a metastasis-related sugar structure. It was increased on H7721 human hepatocarcinoma cells after transfection of the metastasis-promoting gene c-erbB2/neu [10], or treatment with epidermal growth factor [11], whereas it was decreased by the metastasis-suppressive gene nm23H1 [12] or all-trans retinoic acid [11]. The metastatic potential, including cell adhesion to laminin, cell migration through a transwell and cell invasion through a matrigel, was always positively correlated to SLe x expression on the cell surface [10 -12].…”
mentioning
confidence: 99%
“…The Lewis antigens are identifiable with specific monoclonal antibodies and are strongly associated with a number of different tumors (Kurahara et al 1999;Liu et al 2001), particularly lung carcinomas, in which their expression correlates with tumor burden and metastatic potential (Miyake et al 1988;Itai et al 1990). Although expression of Lewis antigens has been described in development of normal lung (Miyake et al 1988;Itai et al 1990), the studies presented here are the first demonstration of expression of the LeX/SSEA-1 antigenic epitope in the pulmonary neuroendocrine lineage.…”
Section: Discussionmentioning
confidence: 99%